Angular insensitive nonreciprocal ultrawide band absorption in plasma-embedded photonic crystals designed with improved particle swarm optimization algorithm - Wang, Yi-Han; Zhang, Hai-Feng (Chinese physics B, 2023)
Using an improved particle swarm optimization algorithm (IPSO) to drive a transfer matrix method, a nonreciprocal absorber with an ultrawide absorption bandwidth and angular insensitivity is realized in plasma-embedded photonic crystals arranged in a structure composed of periodic and quasi-periodic sequences on a normalized scale. The effective dielectric function, which determines the absorption of the plasma, is subject to the basic parameters of the plasma, causing the absorption of the proposed absorber to be easily modulated by these parameters. Compared with other quasi-periodic sequences, the Octonacci sequence is superior both in relative bandwidth and absolute bandwidth. Under further optimization using IPSO with 14 parameters set to be optimized, the absorption characteristics of the proposed structure with different numbers of layers of the smallest structure unit N are shown and discussed. IPSO is also used to address angular insensitive nonreciprocal ultrawide bandwidth absorption, and the optimized result shows excellent unidirectional absorbability and angular insensitivity of the proposed structure. The impacts of the sequence number of quasi-periodic sequence M and collision frequency of plasma 1 ν 1 to absorption in the angle domain and frequency domain are investigated. Additionally, the impedance match theory and the interference field theory are introduced to express the findings of the algorithm.